The teacher's personality as a tool of influence in pedagogical interaction in the process of foreign language communication of students - Grytsyk, Nadia; Shvets, Natalya; Golikova, Oksana (University of Technology, Katowice, 2021)
The leading role of the culturological paradigm in the formation of a graduate of a higher education institution who speaks a sufficient foreign language is determined. The article critically analyzes the strategies of the teacher’s personality as a tool of influence in pedagogical interaction in the process of foreign language communication of students. The analysis of the teacher ‘s personality as the most important factor necessary for effective study of a foreign language is performed and the motivation of students as a pedagogical condition in the process of teaching foreign language communication of students is singled out. Effective methods of work in the process of preparing students are described. In order to study this issue on the teacher’s personality as a tool of influence in pedagogical interaction in the process of foreign language communication of students conducted a quantitative study in the form of questionnaires among PhD students 1-4 years of study of the Faculty of Humanities and Education (National University of Life and Environmental Sciences of Ukraine, Kyiv). The methodical recommendations of modern scientists in Ukraine and teachers from Cambridge Assessment English concerning motivation of training as an important factor in preparation of junior bachelors in institutions of professional higher education of specialty 013 “Primary education” with additional qualification “Primary school teacher, foreign language teacher in primary schools” are taken into account. » and bachelors of specialty 014” Secondary education “(English / German / French / Russian language and literature) and in the education of schoolchildren in general secondary education in the new Ukrainian school.
Keywords: teacher's personality; pedagogical interaction; process of foreign language communication; students' motivation; need; influence